Biologically Active Endotoxins from Salmonella Mutants Deficient in O- and R-Polysaccharides and Heptose - Kim, Yoon Berm (1967)
Well-characterized Salmonella mutants formerly used in biosynthetic studies of lipopolysaccharides were used to study the toxic portion of the complex endotoxin. Endotoxins prepared from wild types and their mutants were tested for their biological activities, including pyrogenicity, lethality, and immunogenicity. There was little difference either in the endotoxin yields or in the toxicities between endotoxins from the wild-type and O-antigen deficient mutants. Endotoxin containing mostly lipid A and keto-deoxyoctonate (KDO) prepared from the mutant deficient in both O- and R-antigens and the backbone sugar, heptose, was biologically active. Possibly because of the difference in solubility in water, the yield of endotoxin from the heptoseless mutant was about 10% of the wild type. There was complete reciprocal cross-immunity between all endotoxins tested. These observations suggest that the common toxic moiety is not present in the O- and R-polysaccharides or the backbone sugar heptose, but rather is associated with the lipid portion of the molecule which includes mostly lipid A and KDO.